Logika Transsendental Kant dan Implikasinya Bagi Kemungkinan Pengetahuaan Islam - Alim Roswantoro (Al-Jami'ah Research Centre, 2000)
This paper tries to reconstruct Immanuel Kant's thought of logic that has been described in his magnum opus,Critique of Pure Reason. In this book, Kant who is well-known as critic and philosopher has successfully reconciled two philosophical trends, namely, rationalism and empiricism. This reconciliation demonstrates his philosophical thought which is full of logical argumentation. He strives to prove the existence of a priori knowledge serving as a basis or his transcendental philosophy. From this basic idea, he then explains his transcendental logics in order to support his n priori knowledge. He shows that knowledge absolutely does not cease on empirical or a posteriori root. After describing Kant's transcendental logics, this writing analizes his fundamental idea as an important contribution to the history of human intellectual. Finally, the writer tries to draw its implication for the possibility of Islamic knowledge.